The Development of Children of Preschool Age in the Visual Arts with the Application Method - Mullajonova Nigina Jamolovna (Researchparks Publishing, 2021)
Visual activities for pre-school children are about developing thought, analysis, synthesis, comparison and generalisation. This article discusses the topic of artistic and aesthetic development of preschool children in the fine arts classes in preschool educational institutions.